2014
DOI: 10.4103/2277-9175.145732
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological aspects of congenital heart disease in central and southern district of Iran

Abstract: Background:Congenital heart disease (CHD) is a major health problem and its prevalence is different around the world. The aim of study was determination of the epidemiological aspects of CHD in central and southern district of Iran.Materials and Methods:In this descriptive and analytical study, 3714 medical records were evaluated from March 21, 2001 to December 18, 2011. Medical records of inpatients from angiography and outpatients in the Heart Clinic of Afshar hospital (a referral hospital in center and sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…In the current study, ASD constitutes 9.8% of congenital anomalies, which is comparable to the results of other studies. The ratio of female to male patients in this study was 1:5, which is lower than that in some studies ( 2 ) but in closer agreement with other reports ( 1 , 6 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, ASD constitutes 9.8% of congenital anomalies, which is comparable to the results of other studies. The ratio of female to male patients in this study was 1:5, which is lower than that in some studies ( 2 ) but in closer agreement with other reports ( 1 , 6 ).…”
Section: Discussionsupporting
confidence: 90%
“…ASD is more common in females than in males ( 1 , 2 ). Several studies have reported spontaneous closure of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…20,26 On the other hand, when considering gender, our results contradict some studies showing female preponderance in congenital heart defects such as VSD, PDA, and ASD. For example, Amel et al, 27 who studied 3714 newborns from the south of Iran, found that a higher proportion of female infants suffered from VSD, PDA, ASD, and TOF. Another article showed a slight preponderance of females in the prevalence of CHD (VSD and PDA) on 2067 patients conducted by Ishikawa et al in China.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in gender in this study were different from the clinical impression that WS had no sex difference. SVAS and VSD incidence difference in gender were used reported (Amel‐Shahbaz et al, 2014; Sadler et al, 2001). Female also showed a comparative advantage in other heart diseases such as myocardial injury and prognosis of some heart diseases (Kanwar & Stehlik, 2020).…”
Section: Discussionmentioning
confidence: 99%